?????? ??????? ???? ????? ?????? ??????? ?? ????? ????? ???????? ??? ???? ???? ????? ????? ???????? ???? ???????? - Muhammad Hafidz (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2018)
This study stems from the problems experienced by the Arabic language teacher in the Amanatul Ummah Pacet Islamic Boarding School. Listening skill is one of the most important language skills, because this skill is the basic skill in communication. Through istening skills, students will get a lot of vocabularies, learns patterns of sentences and structures, receives ideas and concepts, and acquires other skills of language, speaking, reading and writing. Therefore, the researcher wanted to know the effectiveness of the Madarij durus Arabiyah book of Sheikh Mohammed Basri Alawi on students’ listening skill. The methodology of this researchis experimental with pre-test and post-test in one group. And the result of this research indicate that Madarij Durus Arabiyah book is effective inimproving students’ listening abilities, students’ score before using Madarij Durus Arabiyah is 63and after using this book, students’ grade have increased to 96, then this increase is very good level.